Vacuoles release sucrose via tonoplast-localised SUC4-type transporters. - Schneider, Sabine; Hulpke, Sabine; Schulz, A.; Yaron, I.; Höll, Janine; Imlau, Astrid; Schmitt, Bianca; Batz, Stefanie; Wolf, S.; Hedrich, Rainer; Sauer, Norbert (Botanica Acta, 2012)
Arabidopsis thaliana has seven genes for functionally active sucrose transporters. Together with sucrose transporters from other dicot and monocot plants, these proteins form four separate phylogenetic groups. Group-IV includes the Arabidopsis protein SUC4 (synonym SUT4) and related proteins from monocots and dicots. These Group-IV sucrose transporters were reported to be either tonoplast- or plasma membrane-localised, and in heterologous expression systems were shown to act as sucrose/H(+) symporters. Here, we present comparative analyses of the subcellular localisation of the Arabidopsis SUC4 protein and of several other Group-IV sucrose transporters, studies on tissue specificity of the Arabidopsis SUC4 promoter, phenotypic characterisations of Atsuc4.1 mutants and AtSUC4 overexpressing (AtSUC4-OX) plants, and functional comparisons of Atsuc4.1 and AtSUC4-OX vacuoles. Our data show that SUC4-type sucrose transporters from different plant families (Brassicaceae, Cucurbitaceae and Solanaceae) localise exclusively to the tonoplast, demonstrating that vacuolar sucrose transport is a common theme of all SUC4-type proteins. AtSUC4 expression is confined to the stele of Arabidopsis roots, developing anthers and meristematic tissues in all aerial parts. Analyses of the carbohydrate content of WT and mutant seedlings revealed reduced sucrose content in AtSUC4-OX seedlings. This is in line with patch-clamp analyses of AtSUC4-OX vacuoles that characterise AtSUC4 as a sucrose/H(+) symporter directly in the tonoplast membrane.